Darkening vistas: Central retinal artery occlusion post-Arnold Chiari 1 surgery in prone position - Shrinkhal; Arun Gowda Keelara; Arvind Kumar Suman; Suyash Singh; Brijesh Kumar Mishra; Nilakshi Banerjee; Akshay Kumar (The Pan-American Journal of Ophthalmology)
Post-operative vision loss (POVL) following spine surgery in the prone position is rare but has been documented. Various pathophysiological mechanisms have been proposed as potential causes, with associated risk factors identified. This article documents an interesting case of a patient who presented with Chiari 1 malformation and developed central retinal artery occlusion (CRAO) postoperatively. We present the case of a 27-year-old male who underwent foramen magnum decompression with C1–C2 fusion for Chiari I malformation, and experienced sudden vision loss in his left eye postoperatively, attributed to CRAO. Despite stable vital signs and minimal blood loss during surgery, the patient developed CRAO after awakening from anesthesia. Prompt treatment was initiated, resulting in partial recovery of vision. However, challenges in treating CRAO persisted, highlighting the importance of meticulous patient positioning during prone surgeries to prevent such complications. Early detection and intervention are crucial for the potential reversibility of visual loss.